An examination of the factors contributing to participation in online social platforms. Issue 6 (21st November 2016) - Bronstein, Jenny; Gazit, Tali; Perez, Oren; Bar-Ilan, Judit; Aharony, Noa; Amichai-Hamburger, Yair
Abstract : Purpose: The purpose of this paper is to examine participation in online social platforms consisting of information exchange, social network interactions, and political deliberation. Despite the proven benefits of online participation, the majority of internet users read social media data but do not directly contribute, a phenomenon called lurking. Design/methodology/approach: A survey was administered electronically to 507 participants and consisted of ten sections in a questionnaire to gather data on the relationship between online participation and the following variables: anonymity, social value orientation, motivations, and participation in offline activities, as well as the internet's political influence and personality traits. Findings: Findings show that users with high levels of participation also identify themselves, report higher levels of extroversion, openness, and activity outside the internet, the motivations being an intermediary variable in the relationship between the variables value. Originality/value: The study shows that participation in online social platforms is not only related to personality traits, but they are impacted by the nature of the motivations that drive them to participate in the particular social platform, as well as by the interest toward the specific topic, or the type or nature of the social group with whom they are communicating.